2011
DOI: 10.1177/1077546311404728
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of stiffness characteristics of an electromagnetic device

Abstract: An electromagnetic device, consisting of a pair of permanent magnets and a non-magnetic coil, has shown its linear advantages for inducing parametric stiffness excitation in the laboratory. The electromagnetic device powered by a DC coil current acts like a mechanical spring with constant stiffness. The effects of design parameters upon the electromagnetic stiffness and its linear operating range (referred as the stiffness characteristics) are important and crucial for the design and usage of the device. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As the electromagnetic stiffness is linearly proportional to the coil current, k e0 is ascertained as k e0 ¼ ffiffiffi 2 p a 0 I 0 , in which I 0 are the RMS values of the current applying to the electromagnetic device, and a 0 is the current/stiffness proportional coefficient. It is shown that a 0 is independent of the coil current and could be obtained by finite element method once the design parameters of the electromagnetic device are given [15].…”
Section: A Cantilever Beam Subjected To Electromagnetic Stiffness Excmentioning
confidence: 99%
See 1 more Smart Citation
“…As the electromagnetic stiffness is linearly proportional to the coil current, k e0 is ascertained as k e0 ¼ ffiffiffi 2 p a 0 I 0 , in which I 0 are the RMS values of the current applying to the electromagnetic device, and a 0 is the current/stiffness proportional coefficient. It is shown that a 0 is independent of the coil current and could be obtained by finite element method once the design parameters of the electromagnetic device are given [15].…”
Section: A Cantilever Beam Subjected To Electromagnetic Stiffness Excmentioning
confidence: 99%
“…The quantitative relationship between the DC coil current and linear electromagnetic stiffness was obtained utilizing the finite element method, and various design parameters of the electromagnetic device were discussed in [15] for their effects upon the current/stiffness relationship and linear stiffness range. Based upon this, the experimental system was designed in the laboratory, and the parametric instability of the cantilever beam under two electromagnetic excitations was studied experimentally and analytically by the authors [16].…”
Section: Introductionmentioning
confidence: 99%
“…The generator is equivalent to an inductance element, and the magnetic field as a medium makes the generator realize the conversion of electromechanical energy [25]. After Maxwell's creative equation of the electromagnetic field was developed, a new theoretical basis for the study and analysis of the electromagnetic field in the generator was provided.…”
Section: Mathematical Modeling Of the Modified Switsc Fault A Two-dimensional Discretization And Piecewise Interpolationmentioning
confidence: 99%
“…Considerable progress has been made in the study of gear transmission system in recent years [1]. Generally, dynamic characteristics of gear systems are obtained from many numerical techniques such as Lumped Parameter Method (LPM) [2], transfer matrix method [3][4], Finite Element Method (FEM) [5][6], and dynamic substructure method (DSM) [7][8]. Among them, DSM, which was evolved from the substructure modal synthesis (SMS) presented by Hurty and Gladwell [9] in the early 1960s, has been widely used in solving complex structural dynamic problems in engineering.…”
Section: Introductionmentioning
confidence: 99%